Vehicle density based multihop broadcast protocol in VANET - Jia-wei HUANG; Shao-hua ZHONG; Lian-hai LIU; Jian-xin WANG (Tongxin xuebao)
In vehicular ad hoc networks (VANET), the medium access control (MAC) protocol was of crucial importance to provide time-critical multihop broadcast. Contemporary multihop broadcast protocols in VANET usually choose the farthest node in broadcast range as the forwarder to reduce the number of forwarding hops. However, it was demonstrated that the farthest forwarder may experience long contention delay in case of high vehicle density. An IEEE 802.11p-based multihop broadcast protocol vehicle density based forwarding (VDF) was proposed, which adaptively chose the forwarder according to the vehicle density. The evaluation results in safety warning and online game applications show that, VDF could shorten broadcast delay by achieving the proper trade-off between the contention delay and coverage speed.